Hubungan Lingkar Lengan Atas Dengan Kejadian Anemia Pada Ibu Hamil Trimester I Di UPTD Puskesmas Cinere 2021 - Nelli, Ermeida (Journal of Midwifery Tiara Bunda, 2024)
Background : Back pain that occurs in the third trimester of pregnancy along with the enlargement of the uterus, the weight point of the body is more inclined forward so that the pregnant woman adjusts her position to remain balanced, as a result of which the body will try to pull the back to be more backward, the lower spine is more curved (lordosis) and the spinal muscles shorten. One of the nonpharmacological interventions to relieve back pain is the five basic techniques of massage. Massage using these five basic techniques includes effleurage or rubbing, friction or rubbing, petrisage or massage/squeezing, tapotage or patting/tracing, and vibratie or vibrating. Purpose : The study was conducted to determine the effect of five basic massage techniques on the back pain of pregnant women in the third trimester. Methods : The approach to this study is a one group pre test and post test design technique. A total sampling of 32 respondents of pregnant women in the third trimester, who were previously given a Numerical Rating Scale (NRS) questionnaire. The intervention of five basic massage techniques is carried out during patient visits with a duration of approximately 30 minutes. Results : Based on the results of the study on the intensity of back pain in the third trimester before (pre-test) and after (post-test) five basic massage techniques for 30 minutes were given which were analyzed using a spearman rank obtained a p value = 0.000. This shows that the value of p<0.05 which means that there is an influence of the five basic massage techniques on the intensity of back pain of pregnant women in the third trimester. Conclusion : There is an effect of intervention five basic massage techniques on the back pain of pregnant women in the third trimester. Suggestion : It is hoped that the intervention of the five basic massage techniques can be carried out as an alternative to reduce the level of back pain in pregnant women